The Role Of The Capital Structure In Moderating The Size Of The Company And Profitability To Tax Avoidance - Maria Magdalena Sonya Yuliarti; Khomsiyah Khomsiyah (Al-Makki Publisher, 2023)
The aims of this study are as follows: 1) To test the effect of firm size on tax avoidance; 2) To test the profitability of tax avoidance; 3) To examine the extent to which capital structure can moderate the relationship between firm size and tax avoidance; 4) To examine the extent to which capital structure can moderate the relationship between profitability and tax avoidance. The type of research used in this research is causal associative research. The population in this study are consumer goods sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The sample was selected using a purposive sampling method. The analytical method used is multiple linear regression analysis.